The Patchwork of Limmen. A research on the building history of the Dutch Reformed Church of Limmen (Bulletin KNOB, 2005)
The earliest mention of the church of Limmen already dates from the 9th/10th century. In 1108 bishop Burchard of Utrecht grants the church to the chapter of St. Mary of Utrecht. It is supposed that around this period the wooden building was replaced by a hall-church built of tuff. An important part of the tufa western façade of this period has been preserved.In about 1200 a brick tower was built against this facade. This tower used this partially leveled down church façade as its 4th wall. The tower was built in the transition period when the use of tuff was abandoned and replaced by brick. It is one of the earliest and rare examples in Northern Holland of the Romanesque style which is represented in brick only.Shortly after the process of building was finished there were signs of subsidence for which reason inside the hall-church two tufa buttresses were built against the western wall. In that early period brick was not common property yet and in trade it was represented in the same way as tuff.Due to the import of the building materials people were dependant on supply and in case of necessity, they had to use what was available. Approximately 100 years later the building of a new choir was started. In the 14th century this choir was replaced by a new Gothic Choir. This five-sided choir probably had a wooden vault.In the 15th century the tufa hall-church between the tower and the choir was demolished in order to make space for a new nave also with a wooden vault. The new brick facades were covered by the reused tuff of the demolished hall-church. Because of the new height of the nave roof it was necessary to heighten the tower.During the Eighty Years' War the church was stripped by Spanish troops who used the timber for entrenchment in the siege of the nearby city of Alkmaar. Only the wall work was left. After the relief of Alkmaar in 1573 the ruin of the church falls into the hands of the new religion. It is not until 1595 that the Protestant Community is able to partly rebuild the church.This new church got a roof construction with a wooden barrel vault. The tower got a provisional flat roof that in 1660 was substituted by a full-fledged spire. In 1741 the spire was changed again and it obtained its present appearance. Also the tufa covered church-façades were partially repaired with bricks so that they obtained their patchwork appearance.In 1806 the decayed wall of the choir was demolished. In 1868 façades of the tower and the church were plastered in white according to the fashion of that time. In the 20th century the tower and the church were restored several times and, among other things, the façades were stripped of their plasterwork. During the restoration archaeological, building historical and dendrochronological research was carried out.